Absorptive capacity and the propensity to adopt advanced technology: the case of computer integrated manufacturing (CIM) systems. (1st January 2012) - Spanos, Yiannis E.
This paper examines the role of absorptive capacity (AC) on firms' intentions to adopt computer integrated manufacturing (CIM) systems, a particularly complex class of advanced manufacturing technology (AMT). I develop a simple model in which AC is reflected in the stocks of prior related knowledge the firm has accumulated in the past, arguing that these stocks constitute a sine qua non-condition for overcoming the inevitable knowledge barriers posed by advanced technologies to the adopting organisation. Moreover, I put forward the assertion that AC will moderate the influence posed by external environment on adoption decisions. Based on data collected from a sample of 87 Greek manufacturing SMEs, the results confirm these hypotheses: firms with high stocks of pre-existing AMT knowledge are more likely to adopt CIM systems, and they are also more likely to respond positively in environmental stimuli.